Identificação com o agressor: interfaces conceituais e implicações para o estudoda violência sexual infantil - Anna Paula Njaime Mendes (2011)
This paper analyses the identification with the aggressor concept, introduced by Sándor Ferenczi in 1933. In order to deepen this investigation, the following basic notions were chosen based on Ferenczis description of the identification with the aggressor: identification, splitting and introjection. The investigation consisted ofresearch on the identification and splitting concepts within freudian psychoanalysis, in order to compare the utilization of these terms by Ferenczi. Acknowledging the notion of introjection began to be used by Ferenczi, differences in its utilization by the author in 1909/1912 and 1933 were highlighted in this paper. In addition, this paper enumerates important factors that comprise the occurrence of trauma caused bysexual abuse in child psychism, while also trying to understand the identification with the aggressor and, thereby, utilizing the freudian notion of complementary series